THE INFLUENCE OF WORK ETHIC AND CAREER DEVELOPMENT ON PT EMPLOYEE PERFORMANCE. SEMEN BATURAJA TBK PALEMBANG - Bella Selviana; Sabeli Aliya (SEAN Institute, 2023)
This research aims to determine the influence of work ethic and career development on employee performance at PT. Semen Baturaja Palembang. This research uses statistical research methods with a quantitative approach. The population in this research is employees of PT. Semen Baturaja Palembang with a sample size of 111 respondents. The method used in taking samples was simple random sampling. The data measurement technique uses multiple linear regression analysis and coefficient of determination. The research results show that: (1) Partial test results obtained that the T-count for Work Ethic is 2.786, which is greater than the T-table of 1.659, so it can be concluded that Work Ethic has an influence on the performance of PT employees. Semen Baturaja Palembang. (2) The partial test results for Career Development obtained a T-count of 6.779 which is greater than the T-table of 1.659, so it can be concluded that Career Development has an effect on PT Employee Performance. Semen Baturaja Palembang. (3) Simultaneous test results obtained an F-count of 49.447, this value is greater than the F-table of 3.08, so it can be concluded that Work Ethic and Career Development simultaneously have a positive and significant effect on PT Employee Performance. Semen Baturaja Palembang.